О. P. OHLOBLYN: THE ORGANIZATION AND TEACHING ACTIVITIES AT THE KYIV INSTITUTE OF PEOPLE’S EDUCATION (1920-1930TH) - Ляпіна, Олена (Київський національний університет імені Тараса Шевченка, 2024)
Introduction. Oleksandr Ohloblyn is one of the most interesting figures of Ukrainian historiography of the 20th century. Researchers of the historian’s life and work focused primarily on his scientific activity mentioning his teaching work very briefly. Therefore, the purpose of this research is to consider the scientific and organizational aspect of the scientist’s activity at the Kyiv Institute of People’s Education. Methods. General scientific methods – historical, logical, analysis, synthesis and systemic approach, general historical methods – comparative, retrospective, synchronistic, principles of historicism, scientific objectivity, and reliability have allowed to carry out a comprehensive analysis and assessment of the historical context of the given topic. The facts analyzed in this article are considered in development, against the background of a specific historical situation, which involves the method of comparative analysis. A comprehensive approach, problem-chronological, and comparative methods have been used to select and analyze the sources. Results. The article singles out and characterizes two periods of the scientist’s pedagogical activity at KIPE. The main directions of O. Ohloblyn’s work regarding the arrangement of professional training for historians have been analyzed. The creation and development of the Historical Cabinet named after O.M. Lazarevskyi, which O. Ohloblyn considered as a scientific center of Kyiv, the main directions of the historical seminar of the highest type at KIPE have been determined. O. Ohloblyn managed not only to organize several sections of the seminar but also to ensure its professional activity from 1923 to 1929. Conclusions. In 1921–1925, O. Ohloblyn realized himself mainly as a capable organizer of the educational process – he headed and arranged the work of the institute’s main course. On his initiative, the Historical Cabinet named after O.M. Lazarevskyi, which was to become a powerful scientific research center of Kyiv, was created; seminars of a higher type designed to prepare young people for thorough research studies were formed. During 1926–1930, Prof. O. Ohloblyn initiated the creation of a specialized archival seminar for in-depth study of the information potential and features of working with materials of Ukrainian and foreign archives. The main goal of the scientist was to create a scientific school of researchers of the economic history of Ukraine. He almost succeeded, but most of his students died during the period of mass repressions in the second half of the 1930s. O. Ohloblyn had to adapt to the circumstances, changing the subject of his academic studies. Key words: O. Ohloblyn, Kyiv, interwar period, Kyiv Institute of People’s Education, pedagogical activity, historical education, professional training, scientific school.

Вступ. Олександр Оглоблин – одна з найцікавіших постатей української історіографії ХХ ст. Дослідники життя і творчості історика акцентували передусім його наукову діяльність, натомість дуже побіжно згадуючи викладацьку роботу. Отже, мета дослідження – розглянути науково-організаційної аспект діяльності вченого в Київському ІНО. Методи. Загальнонаукові методи – історичний, логічний, аналізу, синтезу та системного підходу, загальноісторичні методи – порівняльний, ретроспективний, синхроністичний, принципи історизму, наукової об'єктивності, достовірності дозволили здійснити всебічний аналіз і оцінку історичного контексту означеної теми. Факти, проаналізовані у даній статті, розглядаються у розвитку, на тлі конкретно-історичної обстановки, що передбачає застосування методу порівняльно-співставного аналізу. При підборі й аналізі джерел були застосовані комплексний підхід, проблемно-хронологічний і компаративний методи. Результати. У статті виділено й охарактеризовано два періоди педагогічної діяльності вченого в КІНО. Аналізуються основні напрями роботи О. Оглоблина щодо організації професійної підготовки істориків. Простежено створення і розбудову Історичного кабінету ім. О.М. Лазаревського, який О. Оглоблин розглядав в якості наукового центру м. Києва, визначено основні напрями роботи Історичного семінару вищого типу при КІНО. О. Оглоблину вдалося не тільки організувати кілька секцій семінару, але й забезпечувати його фахову роботу впродовж 1923-1929 рр. Висновки. У 1921–1925 рр. О. Оглоблин реалізував себе переважно як здібний організатор освітнього процесу – очолив і  налагодив роботу основного курсу інституту. За його ініціативи створюється Історичний кабінет ім. О.М. Лазаревського, що мав стати потужним науково-дослідним центром м. Києва; відбувається становлення семінарів вищого типу, покликаних підготувати молодь до ґрунтовних дослідницьких студій. Упродовж 1926–1930 рр. проф. О. Оглоблин ініціює створення спеціалізованого архівного семінару для поглибленого вивчення інформаційного потенціалу й особливостей роботи з матеріалами українських і зарубіжних архівів. Основна мета вченого – створити наукову школу дослідників економічної історії України. І йому це майже вдалося, але в період масових репресій другої половини 1930-х рр. більшість його учнів загинула, а сам О. Оглоблин змушений був підлаштовуватись під обставини, змінивши тематику своїх академічних студій. Ключові слова: О.Оглоблин, Київ, міжвоєнний період, Київський інститут народної освіти, педагогічна діяльність, історична освіта, фахова підготовка, наукова школа.
О.П.Оглоблин: Організаційна і викладацьку діяльність в Київському інституті народної освіти (1920-1930 рр.)
Keywords: O. Ohloblyn; Kyiv; interwar period; Kyiv Institute of People’s Education; pedagogical activity; historical education; professional training; history of Ukraine; О.Оглоблин; Київ; міжвоєнний період; Київський інститут народної освіти; педагогічна діяльність; фахова підготовка; наукова школа; історія України